2022
DOI: 10.26434/chemrxiv-2022-k3j3f
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Diversifying Amino Acids and Peptides via Deaminative Reductive Cross-Couplings Leveraging High-Throughput Experimentation

Abstract: A deaminative reductive coupling of amino acid pyridinium salts with aryl bromides has been developed to enable efficient synthesis of noncanonical amino acids and diversification of peptides. This method transforms natural, commercially available lysine, ornithine, diaminobutanoic acid (DAB), and diaminopropanoic acid (DAP) to aryl alanines and homologated derivatives with varying chain lengths. Attractive features include scalability, tolerance of pharma-relevant (hetero)aryls and functional groups, applicab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…To compare the scope and limitations against non-electrochemical conditions, 22 the set of aryl bromide substrates shown in Scheme 3 were also evaluated using previously reported non-electrochemical methods with Mn 0 powder or tetrakis(dimethylamino)ethylene (TDAE) as reductants. As illustrated in Scheme 4, use of Mn 0 as the reductant led to lower product LCAPs than obtained using electrochemistry for most substrates.…”
Section: Scheme 4 Dependence Of Arbr Scope On Reaction Conditions Amentioning
confidence: 99%
See 2 more Smart Citations
“…To compare the scope and limitations against non-electrochemical conditions, 22 the set of aryl bromide substrates shown in Scheme 3 were also evaluated using previously reported non-electrochemical methods with Mn 0 powder or tetrakis(dimethylamino)ethylene (TDAE) as reductants. As illustrated in Scheme 4, use of Mn 0 as the reductant led to lower product LCAPs than obtained using electrochemistry for most substrates.…”
Section: Scheme 4 Dependence Of Arbr Scope On Reaction Conditions Amentioning
confidence: 99%
“…These reactions use stoichiometric amounts of metal powders as terminal reductants and enable the use of various alkyl and aryl electrophiles. Readily accessible and bench-stable electrophiles (organic halides, 8,13,23,24 redox-active esters, [25][26][27][28][29] alkylpyridinium salts, [20][21][22][30][31][32][33][34] etc.) have been successfully demonstrated in various Ni-catalyzed reductive cross-coupling reactions (Scheme 1A).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7] In particular, the direct coupling of two electrophiles represents an attractive strategy because it precludes the need to pre-form organometallic nucleophiles (R-M, in which M = [B], [Sn], [Zn], [MgX] etc.). For instance, the groups of Weix, [8][9][10][11] Reisman, [12][13][14] Gong 15,16 and others [17][18][19] together with our prior research [20][21][22] have demonstrated that nickel-catalyzed cross-electrophile couplings are an effective strategy for the construction of new C(sp 2 )-C(sp 3 ) bonds. These reactions use stoichiometric amounts of metal powders as terminal reductants and enable the use of various alkyl and aryl electrophiles.…”
mentioning
confidence: 99%
“…These reactions use stoichiometric amounts of metal powders as terminal reductants and enable the use of various alkyl and aryl electrophiles. Readily accessible and bench-stable electrophiles (organic halides, 8,13,23,24 redox-active esters, [25][26][27][28][29] alkylpyridinium salts, [20][21][22][30][31][32][33][34] etc.) have been successfully demonstrated in various Ni-catalyzed reductive cross-coupling reactions (Scheme 1A).…”
mentioning
confidence: 99%